THE DEVELOPMENT OF POPULARITY OF AGRICULTURAL FACULTIES IN THE HUNGARIAN HIGHER EDUCATION UNTIL 2019 - Finta, Zita; Palkovics, András; Kőszegi, Irén Rita (Journal of Central European Green Innovation, 2020)
Education of agricultural employment in Hungary is less favoured than the education of other industries’ employment as well as the European Union (EU) average. Older managers of the individual farms usually started doing agricultural activity and relied on practical experiences in the absence of any specialized studies. According to the Hungarian Central Statistical Office only 14% of farm managers have specialized studies and 20% of them have higher agricultural education (2012). Experience suggests that the higher the education of agricultural employees, the less likely that they earn a living in the agricultural sector permanently. It is linked to the fact that the average wage in the agriculture is significantly lower than the national average wage. Moreover additional income opportunities are less and less. Other difficulties are the ageing age structure of the agricultural employees and the unpopularity of agriculture among the young people. The rate of older farmers is higher and the rate of younger farmers is lower in Hungary than in the EU. Although age structure usually improves as the farm size grows. In our study we examine how changes the need of young people for higher agricultural education and what tendency is shown towards agricultural trainings from 2001. We carry out our study using data of www.felvi.hu. In the literature review we discuss the number of agricultural employment, the ageing age structure of the agricultural society, the important issue of young farmers and the education of agricultural employment, which problems are the most important and most serious ones of the Hungarian agriculture.